EFEKTIVITAS PENYIDIK BADAN NARKOTIKA NASIONAL SUMATERA UTARA DALAM PEMBERANTASAN TINDAK PIDANA NARKOTIKA - Maria Polla Manalu; Nurmaya R A Simanjuntak (INTELIGENSIA MEDIA, 2025)
Narcotics abuse has become a serious problem that threatens the young generation and the stability of countries, including in Indonesia. Etymologically, narcotics comes from the Greek term